2021
DOI: 10.1016/j.celrep.2021.109228
|View full text |Cite
|
Sign up to set email alerts
|

Replicative senescence dictates the emergence of disease-associated microglia and contributes to Aβ pathology

Abstract: Summary The sustained proliferation of microglia is a key hallmark of Alzheimer’s disease (AD), accelerating its progression. Here, we aim to understand the long-term impact of the early and prolonged microglial proliferation observed in AD, hypothesizing that extensive and repeated cycling would engender a distinct transcriptional and phenotypic trajectory. We show that the early and sustained microglial proliferation seen in an AD-like model promotes replicative senescence, characterized by increa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
164
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(168 citation statements)
references
References 56 publications
4
164
0
Order By: Relevance
“…It is possible that there are mechanisms in place by which the brain is capable of sensing and responding to abnormal microglial density. It is also possible that CSF1-induced proliferation eventually leads to microglial senescence [ 32 ], or that older microglia respond differently to the CSF1 mitogenic signal. Additional studies will be required to distinguish between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that there are mechanisms in place by which the brain is capable of sensing and responding to abnormal microglial density. It is also possible that CSF1-induced proliferation eventually leads to microglial senescence [ 32 ], or that older microglia respond differently to the CSF1 mitogenic signal. Additional studies will be required to distinguish between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulative studies have shown microglia-mediated regulation of plaque deposition and/or p-tau propagation by CSF1R inhibitors. For example, the prevention of early microglial proliferation by a CSF1R inhibitor (GW2580) hinders the development of senescence and disease-associated microglia, impairing the accumulation of Aβ, as well as associated neuritic and synaptic damage ( Hu et al, 2021 ). Moreover, CSF1R-inhibition-mediated microglia deletion protects against plaque-dependent perineuronal nets (PNNs) loss in the AD brain ( Crapser et al, 2020 ), prevents plaque deposition, and improves cognition in different AD-related mouse models ( Dagher et al, 2015 ; Olmos-Alonso et al, 2016 ; Sosna et al, 2018 ; Spangenberg et al, 2019 ).…”
Section: Csf1r In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Rare genetic variants of TREM2 have been identified to impair microglial function and hence identified as risk factors for late-onset AD (Gratuze et al, 2018). It was also reported that replicative senescence of microglia leads to formation of DAM and contributes to early Aβ pathology (Hu et al, 2021).…”
Section: Role Of Microglia In Alzheimer's Disease-associated Neuroinflammationmentioning
confidence: 99%